1978
DOI: 10.1002/j.1879-3479.1977.tb00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Labor with Oral Prostaglandin E2 Tablets

Abstract: Labor was successfully induced by forewater amniotomy and oral administration of prostaglandin E2 tablets in 91.3% of 153 women with singleton pregnancies. Deliveries occurred within 12 hours for more than 90% of the successfully induced patients. Although not statistically significant, a higher pelvic score appeared to be associated with shorter induction-to-delivery intervals. There were no harmful side effects for either mother or baby; only 14.5% experienced minor side effects, primarily gastrointestinal u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
1986
1986

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In some studies, amniotomy was not done until active labor was noted, 58,59 while in others, amni otomy was done routinely at the beginning of in duction 61,62 and their success rates were markedly enhanced (90 to 100%). The effect of simultaneous amniotomy was examined in a retrospective non-randomized study.…”
Section: Oral Administrationmentioning
confidence: 99%
“…In some studies, amniotomy was not done until active labor was noted, 58,59 while in others, amni otomy was done routinely at the beginning of in duction 61,62 and their success rates were markedly enhanced (90 to 100%). The effect of simultaneous amniotomy was examined in a retrospective non-randomized study.…”
Section: Oral Administrationmentioning
confidence: 99%
“…In recent years, prostaglandin has been given intravenously (4) or orally (1,2,5). Both procedures have proven effective for labor induction (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Both Swedish and other studies have shown that PGF2, or PGE2 is at least as effective as oxytocin (33,35,47,48). Oral administration of PGE2 has been studied, but only to a limited extent in combination with early amniotomy (2,15,16,37,50).…”
mentioning
confidence: 99%